From the guest editors - Abba Gumel; James Watmough (Mathematical Biosciences and Engineering)
In September of 2003, on the tail of the outbreak of Severe AcuteRespiratory Syndrome (SARS) in the Greater Toronto Area, MITACS(www.mitacs.ca), one of Canada's Networks of Centres ofExcellence, teamed up with Health Canada in funding a workshopentitled the MITACS-PIMS-Health Canada meeting on SARS atthe magnificent Banff International Research Station (BIRS) . Afollow-up summer school and workshop were held the following year,at the same venue, under the auspices of the PIMS-MITACS-MSRISpecial Program on Infectious Diseases, June 19 to July 02, 2004.Admission into the graduate summer school was quite competitive.Forty three students (10 from USA, 32 from Canada and 1 fromChina, as part of the MITACS exchange program with the ChineseMinistry of Higher Education) were selected.